Planned Behavior Theory Approach to Waste Management Behavior in South Denpasar District - Daniel Beltsazar Jacob; Ni Made Utami Dwipayanti (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2022)
Background: In Bali, waste generation is estimated at 10,266.4 m3 per day. Although promotion and public education about waste management have been carried out for a long time, community behavior related to waste management is still lacking. Objective: This study aims to better understand the factors influencing waste management behavior. Thus, the promotion strategy given to the community can be ideal. Methods: A cross-sectional study was conducted in 5 sub-districts in South Denpasar District. The accessible population was all households in South Denpasar District, with a total of 36,722 households. After calculation according to the formula, the sample size was 100 and was added 10% to make 110 samples to minimize invalid data or unwilling households. As for the exclusion criteria for respondents, they were those who have lived <6 months in the sub-district of South Denpasar. The sampling technique used was Probability Proportional to Size, then analyzed using the logistic regression. The questionnaire was used to help the data collection processes. Results: People with good behavior in managing waste amounted to 55.45%. The multivariate analysis results showed a significant relationship between knowledge (AOR=2.52; 95%CI= 1.08-5.85), attitude (AOR=3.06; 95%CI= 1.13-8.28), and perceived behavior control (AOR=3.00; 95%CI= 1.22-7.38) with waste management behavior in the community. Conclusion: Efforts are needed to increase knowledge through training and education programs managed by the government and local non-governmental organizations. In addition to more frequent programs to increase community participation, accompanied by more adequate facilities and infrastructure such as carrier services and waste banks.